Standardization of Epidemiological Surveillance of Acute Poststreptococcal Glomerulonephritis . (15th September 2022) - Miller, Kate M; Van Beneden, Chris; McDonald, Malcolm; Hla, Thel K; Wong, William; Pedgrift, Helen; Kaslow, David C; Cherian, Thomas; Carapetis, Jonathan R; Scheel, Amy; Seale, Anna; Bowen, Asha C; et al.
Abstract: Acute poststreptococcal glomerulonephritis (APSGN) is an immune complex-induced glomerulonephritis that develops as a sequela of streptococcal infections. This article provides guidelines for the surveillance of APSGN due to group A Streptococcus (Strep A). The primary objectives of APSGN surveillance are to monitor trends in age- and sex-specific incidence, describe the demographic and clinical characteristics of patients with APSGN, document accompanying risk factors, then monitor trends in frequency of complications, illness duration, hospitalization rates, and mortality. This document provides surveillance case definitions for APSGN, including clinical and subclinical APSGN based on clinical and laboratory evidence. It also details case classifications that can be used to differentiate between confirmed and probable cases, and it discusses the current investigations used to provide evidence of antecedent Strep A infection. The type of surveillance recommended depends on the burden of APSGN in the community and the objectives of surveillance. Strategies for minimal surveillance and enhanced surveillance of APSGN are provided. Furthermore, a discussion covers the surveillance population and additional APSGN-specific surveillance considerations such as contact testing, active follow up of cases and contacts, frequency of reporting, surveillance visits, period of surveillance, and community engagement. Finally, the document presents core data elements to be collected on case report forms, along with guidance for documenting the course and severity of APSGN.